OP0231 Heart involvement in scleroderma patients and mice models. (23rd January 2014) - Venalis, P.; Kumánovics, G.; Schulze-Koops, H.; Akhmetshina, A.; Dees, C.; Zerr, P.; Cziriak, L.; Mackevic, Z.; Lundberg, I.E.; Distler, O.; Schett, G.; Distler, J.H.
Abstract : Background: Fibrosis and vasculopathy are the hallmarks of Systemic sclerosis (SSc). There was a shift over SSc-related death causes over last years. Cardiomyopathy was identified as a major cause of death. However, the pathogenesis of SSc-related cardiomyopathy is poorly understood. New therapies as well as platforms for testing are needed Objectives: We aimed to characterize cardiomyopathy in patients and mice models of SSc, and identify the best animal model for SSc-related cardiomyopathy. Methods: Four patients with definite systemic sclerosis were enrolled in the project. Disease duration was 5±2 year. Patients with clinical evidence for cardiovascular disease were excluded from the study. Three systemic disease models of scleroderma were chosen: Fra-2 transgenic mice model (Fra-2), sclerodermatous chronic Graft versus Host disease (cGvHD) model and tight skin 1 mutation model (Tsk-1). Formalin fixed and paraffin embedded heart sections used for IHC. Heart sections from SSc patients, controls and mouse models were stained for α-SMA, CD31, active caspase3, picrosirius and hematoxylin eosin. Results: Significant collagen accumulation was observed in hearts of SSc patients. The fibrotic area was increased in 8.8±2.3 folds compared to controls (P<0.001). Same pattern was found in Fra-2 mice with 8.9±2.8 fold increase (P=0.0002). In contrast, no significant changes were observed in cGvHD and in Tsk-1 mice. To detect differentiation towards myofibroblasts we stained for the α-SMA. SSc samples presented with increased numbers of myofibroblasts 2.5±0.6 vs. 0.5±0.8 (P=0.01) per high power field in controls. Same pattern found in all mice models of SSc, though highest mimicry to SSc hearts observed in Fra-2 model (3.0±1.1 vs. 0.5±0.6 P=0.0005). CD31 stainings revealed significant loss of capillaries in SSc hearts (2.16±0.17 fold change vs. controls P<0.0001). A prominent capillary loss was also observed in Fra-2 tg and in cGvHD models (2.0±0.2 P<0.0001 and 2.1±0.3 P<0.0001 fold change, respectively). No changes were observed in Tsk-1 mice. Apoptosis of endothelial cells was increased in Fra-2 tg mice vs. controls (2.5±0.9 vs. 0.17±0.43 P=0.0001). Apoptosis was observed in cGvHD mice though it was also elevated in controls (2.6±0.7 vs. 1.2±0. 5 P=0.003). No apoptosis was detected in capillaries of Tsk-1 mice. Endothelial apoptosis was also elevated in SSc hearts with 1.2±0.4 vs. 0.2±0.4 (P=0.0018) in controls. Detected higher numbers of perivascular leukocytes in SSc patients (5.8±1.8 fold change, P=0.0001) strengthened the hypothesis of vascular damage. Conclusions: We demonstrate that heart changes were detectable in all models of SSc, but the typical features of cardiac disease in SSc –loss of capillaries due to apoptosis of endothelial cell and fibrosis- were closely mimicked only by Fra-2 tg mice. The cGvHD and Tsk-1 mice lacked some features of scleroderma related cardiomyopathy and were less representative. Thus, Fra-2 tg mice are a promising preclinical model to study the mechanisms and therapeutic approaches of heart involvement in systemic sclerosis. Disclosure of Interest: None Declared